MAINTAINING INDEPENDENCE: HEALTH, DISABILITY, AND STAYING IN-SHAPE. (11th November 2018) - Brady, S; Miller, J; Ward, C; Raue, M; D'Ambroiso, L; Ellis, D; Felts, A; Coughlin, J F
Abstract: Physical well-being is crucial for older adults to maintain their independence and age successfully. This presentation will share results on several dimensions of physical well-being among the MIT AgeLab Lifestyle Leaders. First, the presentation will discuss behaviors related to, perceived benefits of, and barriers to exercise and physical fitness for the oldest old and will explore how their exercise behaviors have changed over time. While most believed physical activity provides extensive benefits and self-identified as regular exercisers, they also identified many barriers. Potential solutions identified by the Lifestyle Leaders, including wearable technology, will be discussed. Second, the presentation will examine changes in vision and hearing the Lifestyle Leaders have experienced, how these changes have affected them, and their reactions to technologies that might mitigate losses in vision and hearing. Changes in vision primarily affected mobility-related activities and functional abilities, whereas changes in hearing affected interpersonal communication and sense of belonging.